Patient-reported outcome measures following revision knee replacement: a review of PROM instrument utilisation and measurement properties using the COSMIN checklist - Sabah, SA; Hedge, EA; Abram, SGF; Alvand, A; Price, AJ; Hopewell, S (BMJ Publishing Group, 2021)
Objectives To identify: (1) patient-reported outcome measures (PROMs) used to evaluate symptoms, health status or quality of life following discretionary revision (or re-revision) knee joint replacement, and (2) validated joint-specific PROMs, their measurement properties and quality of evidence. Design (1) Scoping review; (2) systematic review following the COnsensus-based Standards for selection of health status Measurement INstruments (COSMIN) checklist. Data sources MEDLINE, Embase, AMED and PsycINFO were searched from inception to 1 July 2020 using the Oxford PROM filter unlimited by publication date or language. Eligibility criteria for selecting studies Studies reporting on the development, validation or outcome of a joint-specific PROM for revision knee joint replacement were included. Results 51 studies reported PROM outcomes using eight joint-specific PROMs. 27 out of 51 studies (52.9%) were published within the last 5 years. PROM development was rated ‘inadequate’ for each of the eight PROMs studied. Validation studies were available for only three joint-specific PROMs: Knee Injury and Osteoarthritis Outcome Score (KOOS), Lower Extremity Activity Scale (LEAS) and Western Ontario and McMaster Universities Arthritis Index (WOMAC). 25 out of 27 (92.6%) measurement properties were rated insufficient, indeterminate or not assessed. The quality of supporting evidence was mostly low or very low. Each of the validated PROMs was rated ‘B’ (potential for recommendation but require further evaluation). Conclusion Joint-specific PROMs are increasingly used to report outcomes following revision knee joint replacement, but these instruments have insufficient evidence for their validity. Future research should be directed toward understanding the measurement properties of these instruments in order to inform clinical trials and observational studies evaluating the outcomes from joint-specific PROMs.